Sublethal oligodendrocyte injury: A reversible condition in multiple sclerosis?. Issue 6 (2nd June 2017) - Cui, Qiao‐Ling; Khan, Damla; Rone, Malena; T.S. Rao, Vijayaraghava; Johnson, Radia Marie; Lin, Yun Hsuan; Bilodeau, Philippe‐Antoine; Hall, Jeffery A.; Rodriguez, Moses; Kennedy, Timothy E.; Ludwin, Samuel K.; Antel, Jack P.
Abstract : Objective: Degeneration of oligodendroglial distal processes has been identified as an early event in multiple sclerosis (MS) lesion development. Our objective was to further define the development of the "dying‐back" oligodendrocyte lesion in situ and to model the development and potential reversibility of such responses using dissociated cultures of adult human brain‐derived oligodendrocytes. Methods: In situ analyses were performed on glutaraldehyde‐fixed thin sections of clinically acute and pathologically active cases of MS. In vitro studies were conducted using adult human brain‐derived oligodendrocytes challenged by metabolic stress conditions (low nutrient/glucose). Results: In situ analyses indicated a spectrum of myelin changes in the presence of morphologically intact oligodendrocytes; these included degeneration of the inner cytoplasmic tongue with increasing sizes of intramyelinic bleb formation that could result in radial fractures of the myelin sheath. Macrophages with ingested myelin fragments were identified only once the fragmentation was established. In vitro studies indicated that oligodendrocyte process retraction, which was linked to reduced glycolytic respiratory activity, is reversible until a critical time point. Subsequent cell death was not linked to caspase‐3–dependent programs. Gene expression studies conducted at the latest reversible time point revealed reduced expression of pathways associated with cell process outgrowth and myelination, as well as with metabolic activity. Interpretation: Our findings reveal the potential to protect and possibly restore myelin elaborated by existent oligodendrocytes in early and evolving MS lesions, and suggest the necessity of ongoing studies of the mechanisms underlying subsequent adult human oligodendrocyte cell death. Ann Neurol 2017;81:811–824